2022
DOI: 10.1200/edbk_350292
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Testing for All: Overcoming Disparities in Ovarian Cancer Genetic Testing

Abstract: Nearly 3% of the population carries genetic variants that lead to conditions that include hereditary breast and ovarian cancer and Lynch syndrome. These pathogenic variants account for approximately 20% of ovarian cancer cases, and those with germline pathogenic variants have an odds ratio between 4 and 40 for developing ovarian cancer compared with noncarriers. Given the high prevalence of genetic variants, multiple organizations, including ASCO, recommend universal genetic counseling and testing for women di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
43
1
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(47 citation statements)
references
References 88 publications
0
43
1
3
Order By: Relevance
“…Similarly, we cannot assess any perceptions of intrusion or violation of privacy, as those relatives feeling this way did not provide follow‐up data. Prior literature suggests racial and ethnic disparities in genetic medicine 40–45 . Although our results did not demonstrate disparities, this was a small feasibility trial without a control arm and with limited racial and ethnic diversity.…”
Section: Discussioncontrasting
confidence: 60%
“…Similarly, we cannot assess any perceptions of intrusion or violation of privacy, as those relatives feeling this way did not provide follow‐up data. Prior literature suggests racial and ethnic disparities in genetic medicine 40–45 . Although our results did not demonstrate disparities, this was a small feasibility trial without a control arm and with limited racial and ethnic diversity.…”
Section: Discussioncontrasting
confidence: 60%
“…In Brazil and other low- or middle-income countries, the socioeconomic barrier impact health care access. Despite the worldwide advocacy for broad genetic testing access ( 49 , 50 ), uninsured patients remain a concern. Providing access to genetic testing without assurance of all subsequent preventive and treatment opportunities may bring more harm than benefit ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…Prior research has shown vast increases in the rates of BRCA1/2 testing, partially due to media attention and public awareness campaigns in the past decade (Chen et al, 2018;Martin et al, 2019). Increases in testing, however, persisted among higher income individuals, and many who are at high risk for cancer are still underutilizing clinical testing (Frey et al, 2022;Levy et al, 2011).…”
Section: Discussionmentioning
confidence: 99%